Sistem Pendukung Keputusan Pemilihan E-Wallet Terbaik Menerapkan Metode Simple Additive Weighting (SAW) - Lasria Mandalahi; Rizky Dermawan; Sopi Napidah Sibarani (ADA Research Center, 2024)
The popularity of e-wallets in Indonesia continues to skyrocket along with people's digital lifestyle. Ease of transactions and various attractive promos are the main attractions. However, data security and variations in transaction fees need to be a concern. To help users choose the right e-wallet, the application of a Decision Support System (SPK) by considering factors such as ease of use, security, and cost can be an effective solution. This research develops a Decision Support System (SPK) using the Simple Additive Weighting (SAW) method. This SPK allows Punulis to compare and evaluate various important criteria in choosing an E-Wallet, such as security, ease of use, merchant support, transaction fees, and additional features. The SAW method is used to give weight to each criterion and produce the best E-Wallet recommendations based on the calculations carried out. From the results of calculations using the SAW method, an e-wallet ranking was obtained with Link Aja with a final value of 1.219 as the best, followed by iSaku with a final value of 1.008, and Jenius with a final value of 0.948.